(3GdbUjOI GdRjfjIs - (3Ydj Hf CHj WGdH GdbQTj,J (B40 (3g` s
(3ChdgG (B:s
(3MQeJ MHGdc HYO hUdc RjfH hGdOgQ ajg JUQe hJbdH s
(3BNQgG (B:s
(3hdbO fUMJc Ef bHdJ fUjMJi hGdaUM CYdGekG jHGY hjhgH EfJgJ GdbUjOI GdRjfjI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B295s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdNRGfI GdYGeI HGdQHGW (B_ (3GdeZQH (B(364 D) s
Keywords: (3GdeLGejYs